Prevalencia de Brucella spp en ovinos y posibles factores de riesgo asociados a la enfermedad en la parroquia Cusubamba cantón Salcedo. - Alajo Anchatuña, Vanessa Elizabeth (2021)
Brucellosis is one of the has the greatest impact on the economy and health systemsof nations, for this reason, it is a priority to determine the seroprevalence levels of Brucella spp. in animals that are raised for the production of meat, milk or breedingstock, as an effort to prevent the spread of this disease in animals and its possibletransmission to humans. In this research, adescriptivenonexperimentalcrosssectionalstudywascarriedout,the prevalence of Brucella spp. and associated riskfactors in the flock of sheep from Cusubamba community of the; applying sievetests (Rose Bengal) to blood samples from170 animals, while a survey was appliedto livestock owners, to determine the risk factors associated with the transmissionof diseases in these cattle herds; The results of the samples sent to the laboratoryfor processing were conclusive; none of the samples waspositive for Brucella spp,were confirmed ELISA tests, that were negative for strains B. abortus, B. Melitensisy B. Suis. confirming that there is no prevalence of Brucella spp. inthe flock ofsheep from Cusubamba community.